2007
DOI: 10.1080/10796120701520226
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Adjustment Problems in a National Sample of Adolescents1

Abstract: This study examined a structural equation model of the associations among food insecurity, parental emotional distress, quality of parenting, and adolescents' adjustment problems, controlling for socioeconomic status (SES), sex, and race/ethnicity. Additionally, we examined the relative effects of food insecurity, SES, parental emotional distress, and quality of parenting on adjustment problems. A sample of 11,139 12 Á17-year-olds selected from the 2002 National Survey of American Families data set were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…In a qualitative study, Hamelin, Habicht, and Beaudry [41] found that food insecurity results in disrupted household dynamics evidenced by parental irritability, anger, parental unavailability, and conversation gap with children. Similarly, Ashiabi and O'Neal [42] found that higher levels of food insecurity predicted heightened parental depression, and a reduction in positive parenting behaviors.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a qualitative study, Hamelin, Habicht, and Beaudry [41] found that food insecurity results in disrupted household dynamics evidenced by parental irritability, anger, parental unavailability, and conversation gap with children. Similarly, Ashiabi and O'Neal [42] found that higher levels of food insecurity predicted heightened parental depression, and a reduction in positive parenting behaviors.…”
Section: Introductionmentioning
confidence: 93%
“…Drawing on the family economic stress framework [7] , [9] which suggests that income poverty affect children by limiting their access to material resources, and indirectly by increasing parental depressive symptoms and poor quality parenting, we argue that income poverty and material hardship will be associated with parental depression and parenting behaviors. We contend that income poverty and material hardship may elevate levels of parental depression [8] , [31] , [37] , [40] and adversely affect quality of parenting behaviors [8] , [41] , [42] , and ultimately child health [52] .…”
Section: Introductionmentioning
confidence: 99%
“…In adolescence, food insufficiency has been associated with being suspended from school, having difficulty with other children, having seen a psychologist (Alaimo, Olson, & Frongillo, 2001), increased incidences of socioemotional problems (Ashiabi & O’Neal, 2007), and reports of dysthymia, thoughts of death, desires to die, and suicide attempts among teens (Alaimo, Olson, & Frongillo, 2002). Children’s socioemotional problems or distress may arise through biological mechanisms, such that food insecurity causes or maintains negative affect and depressed mood (Garner, 1997), or it may be a direct function of anxiety about lack of food.…”
Section: Linking Food Insecurity and Children’s Outcomesmentioning
confidence: 99%
“…Given previous research indicating that psychosocial factors predict SSS in adults, we further hypothesize that food insecurity is positively associated with youth SSS. Food insecurity has been associated with adverse physical and psychosocial development issues among youth and emotional distress among parents . Additionally, food insecurity is often accompanied by obesity and is more prevalent in Hispanic households than in non‐Hispanic white households .…”
Section: Introductionmentioning
confidence: 99%